Electromagnetic structure of few-nucleon ground states - Marcucci, L. E. (2016)
Experimental form factors of the hydrogen and helium isotopes, extracted from an up-to-date global analysis of cross sections and polarization observables measured in elastic electron scattering from these systems, are compared to predictions obtained in three different theoretical approaches: the first is based on realistic interactions and currents, including relativistic corrections (labeled as the conventional approach); the second relies on a chiral effective field theory description of the strong and electromagnetic interactions in nuclei (labeled χEFT); the third utilizes a fully relativistic treatment of nuclear dynamics as implemented in the covariant spectator theory (labeled CST). For momentum transfers below $Q\lesssim 5$ fm−1 there is satisfactory agreement between experimental data and theoretical results in all three approaches. However, at $Q\gtrsim 5$ fm−1, particularly in the case of the deuteron, a relativistic treatment of the dynamics, as is done in the CST, is necessary. The experimental data on the deuteron A structure function extend to $Q\simeq 12$ fm−1, and the close agreement between these data and the CST results suggests that, even in this extreme kinematical regime, the study of few-body form factors provides no evidence for new effects coming from quark and gluon degrees of freedom at short distances.